Investigation of virulence factors in resistance and sensitive pseudomonas aeruginosa clinical isolates - Zeinab Waheed kadim; Hala Mouayed Radif (Ibn Al-Haitham Journal for Pure and Applied Sciences)
The pathogen "Pseudomonas aeruginosa" is extremely hazardous for people with weak immune systems because it has several virulence factors and can resist antibiotics. During the time period between October 2022 and February 2023, 102 specimens from different clinical sources, including burn, mid-stream urine, wound, ear, and sputum were collected. From 102 clinical specimens, only 33 isolates (32.35%) of P. aeruginosa were identified by Phenotypic characteristics, a biochemical test, the Vitek-2 compact system, and confirmed by Conventional Polymerase Chain Reaction (PCR). The antibiotic susceptibility test AST was done by the Vitek 2-Compact system. The highest resistance percentages were for Cephalosporin category at 81.8% (Cefotaxime, Ceftazidime, and Cefepime), while the lowest percentage was for the Fluoroquinolone category at 42.4% (Ciprofloxacin and Norfloxacin); 18 (54.5%) of the isolates were categorized as MDR. The production rates of virulence factors investigated in all tested isolates were 100% for protease, hemolysin, and swarming, while the lipase production rate was 48.5%.